A formação da consciência crítico-filosófica na pedagogia histórico-crítica: a contribuição de Dermeval Saviani - Rezende, André Canevalle (Universidade Federal de São Carlos, 2020)
This dissertation contains the results of the research carried out on the concept of philosophical conscience in Historical-Critical Pedagogy (PHC), considering the contributions originated by Dermeval Saviani. The methodological approach is qualitative and was consummated, essentially, through bibliographic research, in order to identify the main references that Saviani adopted to formulate the conception of philosophical conscience in PHC. However, to verify the assertions produced, there was also an interview with the first formulator of the pedagogy under discussion. The general objective of the heuristic endeavor was to rescue the philosophical bases of PHC, which at the present time has sought to consolidate its psychological foundations, embracing historical-cultural psychology. The textual structure adopted in the following exhibition sought to explain what the origins of the concept of philosophy and conscience are for the original formulator of PHC. For this, the works of Marx, Engels, Lenin, Gramsci, Snyders and Vieira Pinto were initially used, pointed out by Saviani as the main sources that he adopted in the formulation of this pedagogy that he understood as counter-hegemonic. Subsequently, we sought to understand what conscience is to Marxism to, finally articulate the concept of critical-philosophical awareness with the “steps” or “moments” of the PHC method, seeking to highlight how critical-philosophical awareness is present in each of them. The main thesis defended is that the critical-philosophical conscience occupies a central position in Historical-Critical Pedagogy, and that, in spite of that, few academic works have dealt with this theme. Based on that, more studies can be done to find out how the philosophical conscience, referred to in this research with Saviani's referendum of “critical-philosophical conscience”, has implications for the so-called final social practice, which in PHC is always a new starting point to the educational process guided by it and the subject that participates in it, it is believed, is at a qualitatively higher level due to the educational work to which it was submitted.
The formation of critical-philosophical consciousness in historical-critical pedagogy: the contribution of Dermeval Saviani
Keywords: Pedagogia histórico-crítica; Dermeval Saviani; Consciência; Filosofia; Historical-Critical Pedagogy; Consciousness; Philosophy; CIENCIAS HUMANAS::EDUCACAO